2021
DOI: 10.3389/fphar.2021.729909
|View full text |Cite
|
Sign up to set email alerts
|

Induction of PI3K/Akt-Mediated Apoptosis in Osteoclasts Is a Key Approach for Buxue Tongluo Pills to Treat Osteonecrosis of the Femoral Head

Abstract: The Buxue Tongluo pill (BTP) is a self-made pill with the functions of nourishing blood, promoting blood circulation, dredging collaterals, and relieving pain. It consists of Angelica sinensis (Oliv.) Diels, Pheretima aspergillum (E.Perrier), Panax notoginseng (Burk.) F. H. Chen, Astragalus membranaceus (Fisch.) Bge, and Glycyrrhiza uralensis Fisch. Various clinical practices have confirmed the therapeutic effect of BTP on osteonecrosis of the femoral head (ONFH), but little attention has been paid to the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Studies have demonstrated that BTPs upregulated the expression of caspase‐3 and bax in osteoclasts, reduced the expression of bcl‐2, and downregulated the levels of p‐Akt and p‐PI3K in a dose‐dependent manner. These findings indicate that BTPs induce PI3K/Akt‐mediated osteoclast apoptosis and preserve bone mass to a certain extent (Wang, Liu, et al, 2021).…”
Section: Effect Of Drugs On Periodontal Cell Deathmentioning
confidence: 86%
“…Studies have demonstrated that BTPs upregulated the expression of caspase‐3 and bax in osteoclasts, reduced the expression of bcl‐2, and downregulated the levels of p‐Akt and p‐PI3K in a dose‐dependent manner. These findings indicate that BTPs induce PI3K/Akt‐mediated osteoclast apoptosis and preserve bone mass to a certain extent (Wang, Liu, et al, 2021).…”
Section: Effect Of Drugs On Periodontal Cell Deathmentioning
confidence: 86%
“…As a supplement or alternative, many TCM herbal formulations are prescribed for GIONFH patients in Chinese clinics or wards to alleviate symptoms and promote bone repair [ [27] , [28] , [29] ]. In recent years, osteoclast inhibition has attracted high interest as a potential preventive or therapeutic strategy for GIONFH [ 15 , 30 , 31 ]. In the present study, the protective effect of CAG on MPS-induced GIONFH in rats was identified, in which suppression of osteoclast hyperactivity may play a critical part.…”
Section: Discussionmentioning
confidence: 99%
“…What's more, enhanced osteoclast activity was proved to be positively correlated with the early progression of GIONFH, with evidence that the increased protein expression of RANKL in necrotic bone is correlated with the progression stage of GIONFH [ 13 ]. Recently, the efficacy of natural osteoclast inhibitors in the prophylaxis and treatment of GIONFH has been evaluated [ [14] , [15] , [16] ], indicative of their positive therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%
“…HIF 1α is found to be upregulated in the ischemic side of the femoral head, and it can act as a positive regulator of Sox9 activity in femoral head osteonecrosis ( Zhang et al, 2011 ). In addition, the PI3K/AKT signaling pathway may play a significant role in the pathogenesis of ONFH by regulating the proliferation and apoptosis of osteoblasts and osteoclasts ( Deng et al, 2019 ; Wang et al, 2021 ). However, analysis of differences in lncRNA GAS5 expression between the osteogenic induction and non-osteogenic induction groups at the same time point would make this more reasonable.…”
Section: Discussionmentioning
confidence: 99%